Coral Reefs of the Southern Gulf of Mexico. - Tunnell, John W., Jr (Harte Research Institute for Gulf of Mexico Studies Series, Sponsored by the Harte Research Institute for Gulf of Mexico Studies, Texas A & M University-Corpus Christi., 2007)
Coral reefs declined worldwide during the 1980s and 1990s, making them perhaps the most endangered marine ecosystem on Earth. This realization spurred John W. Tunnell Jr. and others to write a comprehensive book that would raise awareness of coral reefs and their plight. Tunnell and coeditors Ernesto A. Chávez and Kim Withers present an integrated and broad-ranging synthesis, while Mexican and U.S. experts assess the current state of these fragile systems and offer a framework for their restoration. Beginning with a history of the research done in this region, Coral Reefs of th.